A Lady with Unilateral Painful Orbital Swelling with Possible Euthyroid Graves Ophthalmopathy (The Journal of Ad-din Women's Medical College, 2025)
Background: Thyroid ophthalmopathy is one of the cardinal features of Graves’ disease. But it can also be found in patients with euthyroid, even with hypothyroid status. Case: A twenty-four years old unmarried, non-smoker lady came with complaints of right-sided proptosis for 4 months. The protrusion of her right eye was gradually increasing and there was continuous dull aching pain. There was no history of neck swelling, weakness, palpitation, excessive sweating, weight loss, or tremor. Investigations revealed that she was in euthyroid state but her antibody titer of thyroid stimulating hormone receptor antibody was found beyond the normal range. She was managed conservatively. Conclusion: Euthyroid Graves’ ophthalmopathy is usually a self-limiting condition. However, it can be vision-threatening if proper evaluation and early management are not done.The Journal of Ad-din Women's Medical College; Vol. 12 (2), July 2024; p 26-29